A decision support tool for response to global change in marine systems: the IMBER ‐ ADA pT Framework - Alida Bundy; Ratana Chuenpagdee; Sarah R Cooley; Omar Defeo; Bernhard Glaeser; Patrice Guillotreau; Moenieba Isaacs; Makino Mitsutaku; R Ian Perry (Fish and Fisheries, 2016)
Global change is occurring now, often with consequences far beyond those anticipated. Although there is a wide range of assessment approaches available to address‐specific aspects of global change, there is currently no framework to identify what governance responses have worked and where, what has facilitated change and what preventative options are possible. To respond to this need, we present an integrated assessment framework that builds on knowledge learned from past experience of responses to global change in marine systems, to enable decision‐makers, researchers, managers and local stakeholders to: (i) make decisions efficiently; (ii) triage and improve their responses; and (iii) evaluate where to most effectively allocate resources to reduce vulnerability and enhance resilience of coastal people. This integrated assessment framework, IMBER ‐ ADA pT is intended to enable and enhance decision‐making through the development, a typology of case‐studies providing lessons on how the natural, social and governance systems respond to the challenges of global change. The typology is developed from a database of case‐studies detailing the systems affected by change, responses to change and, critically, an appraisal of these responses, generating knowledge‐based solutions that can be applied to other comparable situations. Fisheries, which suffer from multiple pressures, are the current focus of the proposed framework, but it could be applied to a wide range of global change issues. IMBER ‐ ADA pT has the potential to contribute to timely, cost‐effective policy and governing decision‐making and response. It offers cross‐scale learning to help ameliorate, and eventually prevent, loss of livelihoods, food sources and habitat.

Global change, ensuing vulnerabilities, and social responses in marine environments - Alida Bundy; Ratana Chuenpagdee; Sarah Cooley; Bernhard Glaeser; Liana Talaue McManus (Regional Environmental Change, 2016)